Medical education in COVID period –student feedback and experiences - Agarwal, Jolly; Maheshwari, Sonam; Agrawal, Anurag; Naithani, Manisha; Pant, Mahendra Kumar (Asian Journal of Medical Sciences, 2022)
Background: The pandemic of COVID-19 brought sudden change to online teaching from traditional teaching. This online teaching uses various digital tools. Aims and Objectives: To know the appropriateness of this online teaching, what modifications we need in future from the present-day online teaching, a cross-sectional survey was performed on the students of Government Doon Medical, Dehradun (Uttarakhand). Materials and Methods: A cross-sectional online survey was conducted from July 1 to 7, 2020 with participation of 194 medical students to critically evaluate the feedback of online teaching. Results: During pandemic, online mode of teaching such as online discussions, pre-recorded video, and sharing and uploading material was utilized. Students clearly opine a preference for face-to-face interactions and conventional mode of content delivery. Conclusion: The use of online mode of content delivery in medical colleges enriched by experiences during pandemic has ushered medical education in a novel era. However, further rigorous studies are needed to test the viability of a hybrid technique of teaching as an appropriate way ahead in the future.